Low Impact of Urinary Cortisol in the Assessment of Hydrocortisone Replacement Therapy - Haas, C. S.; Rahvar, A.-H.; Danneberg, S.; Lehnert, H.; Moenig, H.; Harbeck, B. (Hormone and Metabolic Research, 2016)
Hydrocortisone replacement therapy is a cornerstone in the treatment of adrenal insufficiency (AI). While urinary cortisol has been used as a diagnostic tool for AI, it remains unclear whether it is a useful parameter to monitor hydrocortisone replacement therapy. Aim of this study was to evaluate possible differences in cortisol metabolism between adrenal insufficient patients and healthy subjects and to assess the value of urinary cortisol in AI management. In a case-control study, urinary cortisol excretion was determined in 14 patients with primary and secondary AI receiving hydrocortisone infusions from midnight to 8:00 AM. Results were correlated with serum cortisol levels and compared to urinary values obtained from 53 healthy volunteers. Urinary cortisol excretion in healthy subjects was 14.0±7.8 μg/8 h (range: 0.24–35.4), levels did not differ between 3 groups aged 20–34 years, 35–49 years, and ≥50 years. Patients with AI receiving hydrocortisone infusions demonstrated significantly higher rates of urinary cortisol excretion (51.6±37.8 μg/8 h; range 17.1–120.0, p<0.001); the values correlated with serum cortisol levels (r2=0.98). Of interest, patients with secondary AI showed significantly higher serum cortisol levels after hydrocortisone infusion than those with primary AI, conceivably due to residual adrenal function. In conclusion, we showed that: (i) there is a wide inter-individual variability in urinary cortisol excretion rates; (ii) cortisol metabolism in adrenal insufficient patients differs when compared to controls; (iii) there is a strong correlation between urinary and serum cortisol levels; and (iv) urinary cortisol levels despite their variability may help to discriminate between secondary and primary adrenal insufficiency.
Keywords: urinary cortisol; adrenal insufficiency; hydrocortisone replacement therapy